Enterprise Model for Vendor Development: A Study at Selected Technology Park - Ab. Latif, Abdul Aziz; Abdul Rahman, Hamzah Dato (School of Business and Management Institut Teknologi Bandung, 2009)
The study addresses the issues of skills enhancement that need be implemented in three distinct phases of enterprise development. Phase I is the developmental phase where potential entrepreneurs are provided with skills needed for venture take-off or start-up. Phase II is the enterprise creation phase while Phase III is the market development phase. This paper also discusses the multiple roles of the Techno Center during each of these distinct phases. Based on the analysis, the study found that there are gaps across industrial sub-sectors in term of various skills needed to create sustainable enterprise and entrepreneur development. Those gaps are cognitive, interpersonal, technical, creativity, computation, communication, intrapersonal, conceptual, managerial, analytical, technological, acoustic, design, self-management, innovative, basic managerial, supervisory, and marketing. The Techno Centre Enterprise Development Model highlights the central and multiple roles required of The Techno Centre in order to effectively provide support and services during various phases of enterprise development. The services include skill development, networking and linkages services; technology transfer and consultancy services; advisory services; and after-care services have different contents at different stages of the enterprise development.Key words: technology park, sustainable enterprise, technology transfer